More than training: Community‐based participatory research to reduce injuries among hispanic construction workers. Issue 8 (26th March 2013) - Forst, Linda; Ahonen, Emily; Zanoni, Joseph; Holloway‐Beth, Alfreda; Oschner, Michele; Kimmel, Louis; Martino, Carmen; Rodriguez, Eric; Kader, Adam; Ringholm, Elisa; Sokas, Rosemary
Abstract Background Workplace mortality and severe injury are disproportionately distributed among foreign born and Hispanic construction workers. Worker Centers (WCs) provide services and advocacy for low‐wage workers and a way for investigators to reach them. The goal of this project is to prevent occupational injuries by increasing awareness of hazards and self‐efficacy among foreign born, Hispanic construction workers and by expanding the agenda of WCs to include occupational health and safety (H&S). Methods Investigators partnered with eight WCs in seven cities to train worker leaders to deliver a modified OSHA 10‐hr curriculum to their peers. Results Thirty‐two worker leaders trained 446 workers over 3 years. There was a demonstrated improvement in knowledge, hazard identification, self‐efficacy, and sustainable H&S activities. Conclusions This study provides evidence for successful implementation of a training intervention for low wage, low literacy Hispanic construction workers using a community‐based participatory research approach. Am. J. Ind. Med. 56:827–837, 2013. © 2013 Wiley Periodicals, Inc.